The demographics of traumatic brain injury and in-patient cost in high dependency neurosurgical unit: a cross-sectional study in a tertiary academic hospital - Mamo, Dereje Gebrehiwot (My University, 2019)
Background This study looks at Traumatic brain injury (TBI) patient admission regarding the demographics, causes, bed occupancy and costs at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH).CMJAH runs one of the county’s busiest trauma units, and TBI constitutes a significant neuro-surgical admission. Methods It is a retrospective descriptive study on Adult TBI patients admitted to CMJAH in 2015. Data including the demographic characteristics of the patient, date of admission, causes, and type of injury were collected from patient files. Bed occupancy rate of TBI patients was evaluated. Direct ICU and high care costs of TBI patient were calculated. Results A total of 254 cases of TBI were admitted. Most were young males (91.7%) between the ages of 17- 40 years. Blunt head trauma was the cause of 53% of the cases. About 50% of the cases had either acute subdural haemorrhage or acute extradural haemorrhage, and 52% of cases had mild TBI. A neurosurgical intervention was performed in 65% of the cases. A total of 145 TBI cases were admitted to ICU and 186 cases to high care with a bed occupancy rate of 33.4% and 21.8% respectively. The primary cost contributor was ICU stay. The total cost for all TBI patients was estimated to be nearly 16 million rands. The mean in-patient cost for mild, moderate and severe TBI was 48,709.24, R58 499.46 and R86 533.87 respectively. The severity of the injury and surgical intervention did increase the cost of care for individual patients in our study. Conclusion TBI affects younger male predominantly and is mainly caused by blunt trauma to the head. TBI patients occupy a significant proportion of neurosurgical bed. Health care costs for the management of TBI are high and need to be budgeted accordingly.
Academic Head of Department of Neurosurgery, University of Witwatersrand. Head of Department of Neurosurgery, Chris Hani Baragwanath Academic Hospital.